Long life the competence! New "˜Dimensions´ for scientific information´s search and evaluation - Orduña-Malea, Enrique; Delgado-López-Cózar, Emilio (Anuario ThinkEPI, 2018)
After an overview of the changes that are taking place in the world of bibliographic databases used for scientific search and evaluation, this work describes the free version of Dimensions (bibliographic database produced by Digital Science and launched in January 2018). As a first step, a sketch is made of its main characteristics, operations, and features. We conclude that Dimensions is an interesting alternative for the search of scientific information, as well as for the analysis of citations, because it is able to compete with both Scopus (greater coverage and also free of charge) and Google scholar (greater functionalities for the treatment and export of data). Therefore, it is a hybrid product halfway between the classic bibliographic databases and the modern academic search engines.